Anterior Commissure Regulates Neuronal Activity of Amygdalae and Influences Locomotor Activity, Social Interaction and Fear Memory in Mice - Hsu, Tsan-Ting; Huang, Tzyy-Nan; Hsueh, Yi-Ping (Frontiers in Molecular Neuroscience, 2020)
The two hemispheres of the vertebrate brain are connected through several commissures. Although the anterior commissure (AC) is the most conserved white matter structure in the brains of different vertebrates, its complete physiological functionality remains elusive. Since the AC is involved in the connection between two amygdalae and because amygdalae are critical for emotional behaviors and social interaction, we assessed amygdalar activity and function to investigate the physiological role of the AC. We first performed ex vivo electrophysiological recording on mouse brains to demonstrate that the AC delivers a positive signal to facilitate synaptic responses and to recruit basolateral amygdalar neurons via glutamatergic synapses. Transection was then undertaken to investigate the role of the AC in vivo. Results from in vivo optogenetic stimulation suggest that AC transection impairs mutual activation between two basolateral amygdalae. Behavioral analyses were then used to assess if AC surgical lesioning results in hyperactivity, anxiety, social reduction or learning/memory impairment, which are behavioral features associated with neuropsychiatric disorders, such as autism spectrum disorders. We found that AC transection results in higher locomotor activity, aberrant social interaction and reduced associative memory, but not anxiety. Moreover, systemic administration of D-cycloserine, a coagonist of N-methyl-D-aspartate receptor, ameliorated auditory fear memory in AC-transected mice, reinforcing our evidence that the AC potentiates the activity of basolateral amygdalae. Our study suggests that the AC regulates basolateral amygdalar activity and influences neuropsychiatry-related behaviors in mice.